Anti-JCV antibody serostatus and longitudinal evaluation in a Portuguese Multiple Sclerosis population. (November 2017) - Correia, I.; Jesus-Ribeiro, J.; Batista, S.; Martins, A.I.; Nunes, C.; Macário, M.C.; Cunha, L.; Sousa, L.
Highlights: The prevalence of JCV+ was higher in male patients. The seroconversion rate increased with treatment duration. A high fluctuation in the antibody index was observed in seropositive patients. Abstract: Multiple Sclerosis (MS) treatment with natalizumab is associated with Progressive Multifocal Leukoencephalopathy (PML). The risk of PML being related to the anti-JCV antibody index is well established, but there is less known about seroconversion rates in natalizumab-treated patients and longitudinal variation in the anti-JCV antibody index. Our objective was to assess anti-JCV antibody prevalence in an MS population and to evaluate the evolution of the anti-JCV antibody index in natalizumab-treated patients. To assess anti-JCV antibody prevalence, we included all patients who had the anti-JCV antibody test in our consultation, regardless of the treatment. To evaluate the evolution of the anti-JCV antibody index and seroconversion, only natalizumab-treated patients with at least two samples were selected. Demographic characteristics were evaluated. From a total of 371 patients included, 68.19% (n = 253) were seropositive for anti-JCV antibodies (JCV+). There was a significant difference in anti-JCV antibody seropositivity concerning gender (male 76.27% vs. female 64.43%, p = 0.023), but not age. To evaluate seroconversion, 85 patients who were initially seronegative (JCV−) were selected. The annual rate of seroconversion in the first two years was stable, but after that there was a significant increase with treatment duration (ρ = 0.90, p = 0.037): in the first year it was 5.88% (n = 5/85); in the second, 5.71% (n = 4/70); in the third, 6.82% (n = 3/44); in the fourth, 10.34% (n = 3/29); and in the fifth, 15.0% (n = 3/20). The mean index variability was higher in patients who experienced seroconversion (1.16 ± 0.97), followed by JCV+ patients (0.44 ± 0.48), compared to JCV− patients (0.08 ± 0.05). In conclusion, anti-JCV antibody prevalence in our population is comparable to other reported cohorts. The seroconversion rate increased with treatment duration. We found a high fluctuation in the antibody index in JCV+ patients.